Flare (Steel brothers saga, 23,, 2022)
When her own problems converge with those of Brock Steel, the womanizer she has fallen in love with, Rory Pike is drawn into the mysteries surrounding the famous Steel family and is determined to help Brock find the truth no matter what the cost.

Obsession (Steel brothers saga, 2,, 2016)
The continuing story of Jade Roberts and Talon Steel's relationship, with Talon confessing his love for Jade just as she uncovers some surprising information about what the Steel brothers may be hiding from the world.

Possession (Steel brothers saga, 3,, 2016)
Jade Roberts continues her investigation of the Steels, hoping that it will help Talon Steel heal . Meanwhile, Talon works through his history and his fears, hoping that it will bring him closer to Jade. The passion between them is unabated, but the secrets of the past puts both Jade and Talon in danger.

Cherished (Steel brothers saga, 17,, 2021)
Dale Steel has fallen in love with his intern, Ashley White. She's everything he's not, and he's determined to keep her at arm's length. Ashley adores Dale, and wants him to understand he deserves her love. As they work together, their passion grows, and Dale finally agrees to a trial run at a relationship, but a secret from his newfound birth father and an act of God threaten his relationship with Ashley.

Unraveled (Steel brothers saga, 9,, 2018)
Ryan Steel and Ruby Lee are in love, but before they can move forward with a life together, theyre determined to bring resolution to the many unanswered questions they still face. To complicate matters, new threats arise with the arrival of two startling figures from their pasts. As they race against time to find answers, unexpected forces pull them apart. Ryan's brothers, Talon and Jonah, rally to help, wanting to end the struggle and finally bring the last perpetrators to justice. But another riddle surfaces, deepening the rift between Ruby and Ryan. Will they salvage their relationship and finally unravel the mysteries surrounding them?

Insatiable (Steel brothers saga, 12,, 2020)
Marjorie Steel and Bryce Simpson have finally declared their love for each other, but their chance for happiness is once again yanked out from under them. As Marjorie is forced to confront her demons and find an inner strength to save herself and another, Bryce rushes to solve the puzzles his dead father left behind. An ominous lawyer, twins with a secret, and a premature birth present new obstacles as the two lovers scramble to escape the conundrum and leave their families in peace, all while their desire for each other becomes more and more insatiable. When an unexpected figure from the past emerges, leaving them both thunderstruck, the mystery deepens even further.

Ravenous (Steel brothers saga, 11,, 2019)
Bryce Simpson did the only thing he could. He spurned Marjorie Steel. Even though he'll be living on her ranch, he is determined to stay away from her. She's worthy of more than he can even think about giving, especially now that long-buried memories are surfacing and he's learning that his father's sins may go even deeper than he imagined. Bryce's rejection destroys Marjorie, and she descends to a dark place she thought she'd abandoned forever. She emerges stronger, though, and is determined not to let heartbreak rule her life. Change is the answer, she's sure, so she makes plans--plans that include a handsome personal trainer she meets at the gym. When Bryce and Marjorie are thrown together, though, their ravenous hunger for each other takes over, leaving both of them more vulnerable than they realize.

Freed (Steel brothers saga, 18,, 2021)
Dale Steel has spent his life running from the horror of his past, so he's completely unprepared for horror to follow him into the present. But that's exactly what it's done. His only hope is his love for Ashley White, so he grabs hold with both hands, determined to escape his bleak existence. Ashley is so in love she can't see straight. Dale--and the thrall he holds over her--has given her a new outlook on sex and relationships, and she's all in. But Ashley and Dale's troubles are far from over. An untimely death disrupts their hopes at happiness, followed by a phone call that leaves Dale even more grief-stricken. He must make an important decision. Two roads lie in front of him, but only one will free him.

Smolder (Steel brothers saga, 22,, 2022)
Aurora "Rory" Pike gave up her dream of becoming an opera superstar long ago. Now she's content to teach music to the children of Snow Creek while helping her family recover from the wildfire that devastated them. After a messy breakup and a ghost from the past resurfacing, she's examining her priorities...and they don't include a passionate kiss from womanizer Brock Steel. Brock Steel just watched his skirt-chasing mentor-his cousin Donny-give up his playboy ways and fall hard for Callie Pike, sister of Rory Pike, the most beautiful woman in Snow Creek. Rory just ended a relationship, and Brock makes sure he's there to pick up the pieces. Physically, that is. Emotionally? Brock doesn't do emotion. Chemistry between Brock and Rory proves to be hotter than either of them imagined, and it provides a welcome respite, especially for Brock, who's dealing with a conundrum. As bits and pieces of seemingly unrelated evidence emerge, he must come to terms with the fact that his renowned family may not be the paragon he thought they were.

Spark: (Steel Brothers Saga, ,, 2021)
He'll do anything for his family... Donovan "Donny" Steel is on a partnership track with a major Denver law firm. He loves his city career and his luxurious downtown loft, and life is going just how he planned it...until his mother, the city attorney for his hometown of Snow Creek, Colorado, asks him to move back and work for her when her assistant retires. Mom asks? Donny goes. Because he'll do anything for the family who took him in twenty-five years ago. The fact that he can pick up where he left off with gorgeous Callie Pike is simply a fringe benefit. Caroline "Callie" Pike was looking forward to finally beginning law school at age twenty-six, but the western slope fire that destroyed most of her family's vineyards put that plan on hold. At least she has Donny Steel's return to look forward to. After she spent an evening with him at a recent party, he hasn't strayed far from her mind. When Donny and Callie meet again, sparks do more than fly. They shoot like rockets to the stars. But their chemistry can't protect them from the emerging mysteries regarding the Steel family's past...or the secret Callie is keeping as well.

Twisted (Steel brothers saga, 8,, 2017)
Ryan Steel, his world recently upended by an earth-shattering secret, now faces yet another potential revelation surrounding the Steel family mystery. He no longer fully trusts his siblings or the woman he loves. He's alone---alone and terrified and immersed in a conundrum that becomes more twisted each day. Ruby Lee loves Ryan and desperately wants to help him. She'll do whatever she must to see him through this troubling time, but her own shrouded past still haunts her, and she's determined to put an end to both of their mysteries once and for all. But the more she uncovers, the more danger she's in...and she may lose Ryan forever.